A Mesoporous Carbon‐Supported Pt Nanocatalyst for the Conversion of Lignocellulose to Sugar Alcohols. Issue 12 (13th November 2013) - Park, Dae Sung; Yun, Danim; Kim, Tae Yong; Baek, Jayeon; Yun, Yang Sik; Yi, Jongheop
Abstract The conversion of lignocellulose is a crucial topic in the renewable and sustainable chemical industry. However, cellulose from lignocellulose is not soluble in polar solvents, and is, therefore, difficult to convert into value‐added chemicals. A strategy to overcome this drawback is the use of mesoporous carbon, which enhances the affinity between the cellulose and the catalyst through its abundant functional groups and large uniform pores. Herein, we report on the preparation of a Pt catalyst supported on a type of 3D mesoporous carbon inspired by Echinometra mathae (Pt/CNE) to enhance the interaction between the catalyst and a nonsoluble reactant. In the hydrolytic hydrogenation of cellulose, the abundant oxygen groups of CNE facilitated the access of cellulose to the surface of the catalyst, and the open pore structure permits cello‐oligomers to effectively diffuse to the active sites inside the pore. The highly dispersed Pt performed dual roles: hydrolysis by in situ generating protons from H2 or water as well as effective hydrogenation. The use of the Pt/CNE catalyst resulted in an approximately 80 % yield of hexitol, the best performance reported to date. In direct conversion of hardwood powder, the Pt/CNE shows good performance in the production of sugar alcohols (23 % yield). We expect that the open‐structured 3D carbon will be widely applied to the conversion of various lignocellulosic materials.